Assessing the Barley Genome Zipper and Genomic Resources for Breeding Purposes. Issue 3 (1st November 2015) - Silvar, Cristina; Martis, Mihaela M.; Nussbaumer, Thomas; Haag, Nicolai; Rauser, Ruben; Keilwagen, Jens; Korzun, Viktor; Mayer, Klaus F.X.; Ordon, Frank; Perovic, Dragan
Abstract : The aim of this study was to estimate the accuracy and convergence of newly developed barley ( Hordeum vulgare L.) genomic resources, primarily genome zipper (GZ) and population sequencing (POPSEQ), at the genome‐wide level and to assess their usefulness in applied barley breeding by analyzing seven known loci. Comparison of barley GZ and POPSEQ maps to a newly developed consensus genetic map constructed with data from 13 individual linkage maps yielded an accuracy of 97.8% (GZ) and 99.3% (POPSEQ), respectively, regarding the chromosome assignment. The percentage of agreement in marker position indicates that on average only 3.7% GZ and 0.7% POPSEQ positions are not in accordance with their centimorgan coordinates in the consensus map. The fine‐scale comparison involved seven genetic regions on chromosomes 1H, 2H, 4H, 6H, and 7H, harboring major genes and quantitative trait loci (QTL) for disease resistance. In total, 179 GZ loci were analyzed and 64 polymorphic markers were developed. Entirely, 89.1% of these were allocated within the targeted intervals and 84.2% followed the predicted order. Forty‐four markers showed a match to a POPSEQ‐anchored contig, the percentage of collinearity being 93.2%, on average. Forty‐four markers allowed the identification of twenty‐five fingerprinted contigs (FPCs) and a more clear delimitation of the physical regions containing the traits of interest. Our results demonstrate that an increase in marker density of barley maps by using new genomic data significantly improves the accuracy of GZ. In addition, the combination of different barley genomic resources can be considered as a powerful tool to accelerate barley breeding.